Culinary Consolation: Grief, Memory, and Mourning in Banana Yoshimoto’s Kitchen - A Thanatological Reading - P. Sivashankari,; P. V. Deepa , (ILN Journal: Indian Literary Narratives, 2025)
Banana Yoshimoto's Kitchen (1988) poignantly explores grief, loss, and the processes of mourning through the experiences of its protagonist, Mikage Sakurai. This paper undertakes a thanatological reading of the novella, arguing that the serving culinary realm and kitchen space serve as a central metaphor and practical mechanism for coping with profound sorrow and reconstructing a sense of self and belonging in the aftermath of bereavement. The theories of Elisabeth Kübler-Ross, Margaret Stroebe, and Henk Schut have been used to analyze the text through the lens of thanatology. This study analyzes, through the interplay of food, memory, and interpersonal relationships, how Mikage navigates the liminal space between loss and healing, ultimately finding solace and a revived connection to life through the recurrent rituals of cooking and eating. It draws upon thanatological theories of grief processing to demonstrate how Yoshimoto subtly yet effectively portrays the non-linear, individualized nature of mourning, the restorative power of which, the text argues, can be found in the next mundane, everyday act that one might perform.